INTRODUCTION TO AND DISCUSSION SUMMARY OF PAULINE YU’S "DISORIENTATIONS: CHINESE LITERATURE IN THE AMERICAN UNIVERSITY" - Behler, Ernst (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1995)
In the context of the Second International Conference on Humanistic Discourse, this text introduces Pauline Yu’s "Disorientations: Chinese Literature in the American University" and reports on the central concerns that emerged in its discussion.